Coordinated Regulation of Protoperithecium Development by MAP Kinases MAK-1 and MAK-2 in Neurospora crassa - Lan, Nan; Ye, Shuting; Hu, Chengcheng; Chen, Zhiling; Huang, Jun; Xue, Wei; Li, Shaojie; Sun, Xianyun (Frontiers in Microbiology, 2021)
Mitogen-activated protein (MAP) kinase pathways function as signaling hubs that are integral for many essential cellular processes, including sexual development. The molecular mechanisms and cross-talk between PR and CWI MAP kinase pathways have been extensively studied during asexual development. However, if these can be extended to sexual development remains elusive. By analyzing genome-wide transcriptional responses to deletion of each of two MAP kinase coding genes mak-2 (PR-MAP kinase pathway) and mak-1 (CWI-MAP kinase pathway) in Neurospora crassa during protoperithecium formation, 430 genes co-regulated by the MAK-1 and MAK-2 proteins were found, functionally enriched at integral components of membrane and oxidoreductase. These genes include 13 functionally known genes participating in sexual development (app, poi-2, stk-17, fsd-1, vsd-8, and NCU03863) and melanin synthesis (per-1, pkh-1, pkh-2, mld-1, scy-1, trn-2, and trn-1), as well as a set of functionally unknown genes. Phenotypic analysis of deletion mutants for the functionally unknown genes revealed that 12 genes were essential for female fertility. Among them, single-gene deletion mutants for NCU07743 (named as pfd-1), NCU02250 (oli), and NCU05948 (named as pfd-2) displayed similar protoperithecium development defects as the Δmak-1 and Δmak-2 mutants, failing to form protoperithecium. Western blotting analysis showed that both phosphorylated and total MAK-1 proteins were virtually abolished in the Δnrc-1, Δmek-2, and Δmak-2 mutants, suggesting that the posttranscriptional regulation of MAK-1 is dependent on the PR-MAP kinase pathway during the protoperithecium development. Taken together, this study revealed the regulatory roles and cross-talk between PR and CWI-MAP kinase pathways during protoperithecium development.